Tunable polarization-drived superior energy storage performance in PbZrO3 thin films - Tiandong Zhang; Zhuangzhuang Shi; Chao Yin; Changhai Zhang; Yue Zhang; Yongquan Zhang; Qingguo Chen; Qingguo Chi (Journal of Advanced Ceramics, 2023)
Antiferroelectric PbZrO3 (AFE PZO) films have great potential to be used as the energy storage dielectrics due to the unique electric field (E)-induced phase transition character. However, the phase transition process always accompanies a polarization (P) hysteresis effect that induces the large energy loss (Wloss) and lowers the breakdown strength (EBDS), leading to the inferior energy storage density (Wrec) as well as low efficiency. In this work, the synergistic strategies by doping smaller ions of Li+–Al3+ to substitute Pb2+ and lowering the annealing temperature (T) from 700 to 550 ℃ are proposed to change the microstructures and tune the polarization characters of PZO films, except to dramatically improve the energy storage performances. The prepared Pb(1−x)(Li0.5Al0.5)xZrO3 (P(1−x)(L0.5A0.5)xZO) films exhibit ferroelectric (FE)-like rather than AFE character once the doping content of Li+–Al3+ ions reaches 6 mol%, accompanying a significant improvement of Wrec of 49.09 J/cm3, but the energy storage efficiency (η) is only 47.94% due to the long-correlation of FE domains. Accordingly, the low-temperature annealing is carried out to reduce the crystalline degree and the P loss. P0.94(L0.5A0.5)0.06ZO films annealed at 550 ℃ deliver a linear-like polarization behavior rather than FE-like behavior annealed at 700 ℃, and the lowered remanent polarization (Pr) as well as improved EBDS (4814 kV/cm) results in the superior Wrec of 58.7 J/cm3 and efficiency of 79.16%, simultaneously possessing excellent frequency and temperature stability and good electric fatigue tolerance.